Calcium anacardate as growth promoter for piglets at the nursery phase - Matos, Amanda Veruska Silva de; Watanabe, Pedro Henrique; Freitas, Ednardo Rodrigues; Santos, Kassia Moreira; Araújo, Lina Raquel Santos; Nepomuceno, Rafael Carlos; Veira, Alini Mari; Vieira, Eloisa Helena Mendes (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effects of the dietary inclusion of calcium anacardate on the performance, diarrhea incidence, blood parameters, intestinal morphometry, and pH of gastrointestinal contents in piglets from 21 to 42 days of age. Sixty weaned Topigs piglets, with initial weight of 6.049±0.311 kg, were distributed in the following treatments: diet with or without antibiotic growth promoter (zinc bacitracin) and diets supplemented with increasing levels of calcium anacardate (0.4, 0.8, and 1.2%), with six replicates and two animals per experimental unit. No differences in performance (21 to 42 days of age), blood parameters, and villus height:crypt depth ratio were found between piglets fed diets containing calcium anacardate or antibiotic growth promoter. The replacement of the antibiotic growth promoter zinc bacitracin by calcium anacardate results in similar performance in piglets from 21 to 42 days of age, without changes in blood parameters and in the villus height:crypt depth ratio. The dietary inclusion of calcium anacardate does not decrease diarrhea incidence compared with the antibiotic zinc bacitracin.